Peran Pinjaman Luar Negeri Dalam APBN Pada Pembiayaan Pembangunan di Indonesia - Ussa’diyah, Nisa; Vidriza, Ullya; Sua’idy, Ahmad (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
In practice, foreign loans can provide great benefits, especially in their role in financing development, especially in terms of catching up with the Indonesian state among other countries. Indonesia has various potential resources, both natural and human, which are able to support the success of development. Especially in the infrastructure, education and health sectors in an effort to improve the quality of human resources so that they are able to utilize natural resources as well as possible which will later provide full benefits for the survival of the Indonesian people, especially in increasing the Human Development Index (IPM). The government has committed to supporting development by allocating funds to the APBN. However, the great need forced the government to find a solution to cover the lack of financing, among others, by withdrawing foreign loans. This study aims to find out more about the role of foreign loans in the APBN in financing development in Indonesia. The research was conducted using descriptive qualitative methods, where finding answers was carried out through literature study using theory or literature so that it could provide an overview of certain aspects of the population being studied.